PUBLIC COST AND INTERNAL EFFICIENCY IN KWARA STATE PUBLIC SECONDARY SCHOOLS, NIGERIA - Abdulkareem, A. Y.; Atolagbe, A. A.; Akinnubi, O.; Afolabi, S. (Sokoto Educational Review, 2017)
There are 187 public secondary schools in Kwara State, Nigeria out of which 100 were randomly selected. “Secondary Education Cost and Internal Efficiency Checklist" (SECIEC) was used to collect data. Five research questions and one hypothesis were raised and analysed using percentage and- Pearson Product Moment Correlation Coefficient at 0.05 alpha level. The study revealed that budgetary allocations as the main source of funds to secondary schools which dropped annually from 29.2 % of total cost in 2005 to 7.7% in 2009. A significant relationship existed between public cost and internal efficiency in the schools (r=0.623; p < 0.05, df= 98). It was recommended that government should mobilize special funds to expand and renovate the available school facilities.